RETRACTED : Exploring Imami Shia Perspectives on the Quran in Bihar Al-Anwar by Al-Majlisy as a Reference for Understanding the Quran - Yusuf, Muhammad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2023)
This article has been retracted at the request of the Editor-in-Chief. Please see correcting the record https://ejournal.uin-suka.ac.id/ushuluddin/alquran/ethic#correcting Reason: This article contains some duplicate material of a paper that was originally published in Jurnal Penelitian Keislaman, Vol. 7, No. 1, Desember 2010: 1-28 https://www.academia.edu/35877133/TAFSIR_ESOTERIK_AL_MAJLISIY_DALAM_BIH%C3%82R_AL_ANW%C3%82R One of the conditions of submission of a paper for publication is that authors declare explicitly that all of their work is original and has not appeared in a publication elsewhere. We apologize to readers of the journal that this was not detected during the submission process.